Synthesis, anti-plasmodial and cytotoxic evaluation of 1H-1, 2, 3-triazole/acyl hydrazide integrated tetrahydro-β-carboline-4-aminoquinoline conjugates. Issue 2 (15th January 2020) - Sharma, Bharvi; Kaur, Simranjeet; Legac, Jenny; Rosenthal, Philip J.; Kumar, Vipan
Graphical abstract: Abstract: A series of 1 H -1, 2, 3-triazole/acylhydrazide-tethered tetrahydro- β -carboline-4-aminoquinoline conjugates was synthesized with an aim to study their anti-plasmodial structure-activity relationship. The presence of 1 H -1, 2, 3-triazole-core along with a flexible alkyl chain length on aminoquinoline core has favourable influence on the anti-plasmodial activity against Chloroquine-resistant W2 strain of P. falciparum while the introduction of hydrazine core not only diminished the activities but also resulted in increased cytotoxicity against mammalian Vero cells.